Distribution Characteristics of Soil Viruses Under Different Precipitation Gradients on the Qinghai-Tibet Plateau - Cao, Miao-Miao; Liu, Si-Yi; Bi, Li; Chen, Shu-Jun; Wu, Hua-Yong; Ge, Yuan; Han, Bing; Zhang, Li-Mei; He, Ji-Zheng; Han, Li-Li (Frontiers in Microbiology, 2022)
Viruses are extremely abundant in the soil environment and have potential roles in impacting on microbial population, evolution, and nutrient biogeochemical cycles. However, how environment and climate changes affect soil viruses is still poorly understood. Here, a metagenomic approach was used to investigate the distribution, diversity, and potential biogeochemical impacts of DNA viruses in 12 grassland soils under three precipitation gradients on the Qinghai-Tibet Plateau, which is one of the most sensitive areas to climate change. A total of 557 viral operational taxonomic units were obtained, spanning 152 viral families from the 30 metagenomes. Both virus-like particles (VLPs) and microbial abundance increased with average annual precipitation. A significant positive correlation of VLP counts was observed with soil water content, total carbon, total nitrogen, soil organic matter, and total phosphorus. Among these biological and abiotic factors, SWC mainly contributed to the variability in VLP abundance. The order Caudovirales (70.1% of the identified viral order) was the predominant viral type in soils from the Qinghai-Tibet Plateau, with the Siphoviridae family being the most abundant. Remarkably, abundant auxiliary carbohydrate-active enzyme (CAZyme) genes represented by glycoside hydrolases were identified, indicating that soil viruses may play a potential role in the carbon cycle on the Qinghai-Tibet Plateau. There were more diverse hosts and abundant CAZyme genes in soil with moderate precipitation. Our study provides a strong evidence that changes in precipitation impact not only viral abundance and virus–host interactions in soil but also the viral functional potential, especially carbon cycling.